Review Of Certification Of River Ship Operation In Port Branch, Lampung Central Regency - Sri Kelana; Broto Priyono; Rahut Sianturi (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2022)
Branch Port is a river port located in Central Lampung Regency and managed by the Central Lampung Regency Transportation Service. This port connects people who want to cross from Central Lampung Regency to Tulang Bawang Regency and vice versa. Manning Certification serves to find out how many crew members have registered and have met the manning qualifications in accordance with applicable regulations. In this study, researchers used qualitative research with an evaluative descriptive approach to find problems regarding the fulfillment of crewing certification, the obstacles experienced by crew members and what efforts can be made to provide more effective and efficient manning certificate registration services. Currently, the percentage of crew members who have a crewing certificate, which is 100%, has not yet completed a crewing certification. In addition, there were reasons given by the crew in fulfilling the manning certificate, namely 58% said they were rarely checked by officers, 26% did not understand the importance of certificates, 16% did not understand that a certificate of proficiency was mandatory. In addition to the reasons there are obstacles experienced by crew members in making manning certificates, namely 21% said the place of making the certificate was far away, 53% said there was no cost, 26% said there was a lack of information on making manning certificates. Currently, there is no government agency providing manning certificate registration services. So there is a need for a review of the manning of ships in accordance with the Regulation of the Director General of Land Transportation Number KP.3424/AP.402/DRJD/2020 concerning River and Lake Vessels which states that crew members must have a manning certificate. It is very important to provide information and procedures for making certificates, organizing shipping safety training and providing certification services with a Web -based online system.